(untitled) (The Pretoria Student Law Review, 2021)
Section 26 of the Labour Relations Act gives employers and employers’ organisations the power to conclude closed shop agreements through collective agreements with representative trade unions. The closed shop agreement is known as a union security agreement which has been defined as: [a] generic term for an agreement between an employer and a union or unions in terms of which union membership or, alternatively, payment of union subscription is a condition of employment for all employees. Therefore employees are forced to join the representative trade union subject to the conditions being met in section 26(3) of the Labour Relations Act. This has resulted in a lot of debate on whether closed shop agreements are violating the right to freedom of association, or simply limiting it. This article takes the debate further by not only looking at the right to associate, but also looking at this right as a correlative right because ‘freedom of association buttresses and makes good the promise of a variety of other rights.’ Rights such as labour relations rights and political rights rely on the right to associate. Their dependence on the right to associate means that they have to be looked at when determining if closed shop agreements violate or limit the right to associate.